Beyond feminist aesthetics: Feminist literature and social change - Felski, Rita (Harvard University Press., 1989)
Beyond Feminist Aesthetics has a dual focus. First, Rita Felski gives a critical account of current American and European feminist literary theory, and second, she offers an analysis of contemporary fiction by women, drawing in particular on the genres of the autobiographical confession and the novel of self-discovery, in order to show that this literature raises questions for feminism that cannot be answered in terms of a purely gender based analysis. Felski argues that the idea of a feminist aesthetic is a nonissue that feminists have needlessly pursued; she suggests, in contrast, that it is impossible to speak of “masculine” and “feminine,” “subversive” and “reactionary” literary forms in isolation from the social conditions of their production and reception. The political value of such works of literature from the standpoint of feminism can be determined only by an investigation of their social functions and effects in relation to the interests of women in a particular historical context. This leads her to argue for an interdisciplinary approach to the analysis of literature which can integrate literary and social theory, and to develop such an approach by drawing upon the model of a feminist counter-public sphere. Rita Felski has produced a closely reasoned, stimulating book that creates a new framework for discussing the relationship between literature and feminist politics. It will interest students and teachers of women’s studies, comparative literature, cultural studies, and fiction.
Keywords: 1900-1999; changement social; cours; discipline; fem1000; occident; premier cycle; périodes historiques; thématiques; écriture des femmes*; études littéraires

Le rapt de Ganymède - Fernandez, Dominique (Bernard Grasset, 1989)
"D'après la mythologie grecque, Ganymède était le plus bel adolescent vivant sur la terre. Zeus, le dieu suprême, étant tombé amoureux du jeune homme, prit la forme d'un aigle pour l'enlever et en faire son compagnon dans le ciel. Le rapt de Ganymède est resté le symbole de l'audace nécessaire à un amour qui défie les règles communes. Quand j'étais étudiant, deux mots étaient synonymes : homosexuel et paria. Aux hommes et aux femmes de ma génération a manqué la possibilité de découvrir, chez des modèles que le monde entier admire, une légitimation de goûts que l'opinion publique réprouve sous l'épithète de "contre nature". J'ai voulu montrer, d'une part que la persécution de l'homosexualité à partir du XIXe siècle s'explique par des raisons exclusivement économiques et politiques, d'autre part que certains des plus grands esprits, des meilleurs poètes et romanciers, compositeurs de musique, peintres et cinéastes de tous les temps, de Sapho à Platon, de Whitman à Cavafy, de Melville à Yourcenar, du Caravage à David, de Mozart à Schubert, d'Eisenstein à Visconti, ont tissé un réseau d'oeuvres qui peuvent servir désormais de culture, c'est-à-dire d'exemple et d'encouragement. Bien mieux que les paternes et hypocrites absolutions prononcées depuis cent ans par les psychiatres et psychanalystes, véritable imposture de notre temps, dévoilée ici dans un sottisier réjouissant. D.F." -- Site de l'éditeur
Keywords: 1800-1899; 1900-1999; DIG; LGBTQIA2+; approches et analyses; arts; beaux-arts; cinéma; cours; discipline; europe; his4860; histoire; histoire de l'art; histoire et politique; homophobie; hétérosexisme; identités LGBTQIA2+; littérature homosexuelle; musique; mythologie; premier cycle; périodes historiques; régions géographiques; sciences humaines; sexualité; sexualités dissidentes; systèmes d'oppressions; thématiques

Toute écriture est amour - Gagnon, Madeleine; Verthuy, Maïr.; Maranda, Jeanne (Autographie, 1989)
Depuis Les Mots vivants en 1969, Madeleine Gagnon a publié plusieurs livres importants dont Lueur, Les Fleurs du Catalpa et Femmeros. Madeleine Gagnon a colligé, dans Autographie I, des textes de fiction publiés entre 1969 et 1981. Autographie II rassemble les textes de réflexion et critiques écrits parallèlement à son œuvre de fiction.
Keywords: 1900-1999; amériques; arts; canada; cours; discipline; lit3220; premier cycle; périodes historiques; québec; régions géographiques; thématiques; écriture des femmes*; études littéraires

Malaise et révolte des femmes dans la littérature québécoise depuis 1945 - Saint-Martin, Lori; Université Laval Groupe de recherche multidisciplinaire féministe (Cahiers de recherche du GREMF, 1989)
Keywords: 1900-1999; 1940-1949; 1950-1959; 1960-1969; 1970-1979; 1980-1989; amériques; arts; canada; cours; discipline; lit3495; premier cycle; périodes historiques; québec; régions géographiques; thématiques; écriture des femmes*; études littéraires

Woman, native, other: Writing postcoloniality and feminism - Trinh, T. Minh-Ha (Indiana University Press., 1989)
"" ... Methodologically innovative ... precise and perceptive and conscious ... ""--Text and Performance Quarterly""Woman, Native, Other is located at the juncture of a number of different fields and disciplines, and it genuinely succeeds in pushing the boundaries of these disciplines further. It is one of the very few theoretical attempts to grapple with the writings of women of color.""--Chandra Talpade Mohanty""The idea of Trinh T. Minh-ha is as powerful as her films ... formidable ... ""--Village Voice"" ... its very forms invite the reader to participate in the effort to understand how language
Keywords: 1900-1999; approches et analyses; arts; cours; discipline; fem1000; fem3200; féminisme décolonial; littérature; premier cycle; périodes historiques; ressource en ligne; thématiques; écriture des femmes*; études littéraires

Woman, native, other: writing postcoloniality and feminism - Trinh, T. Minh-Ha (Indiana University Press, 1989)
" . . . methodologically innovative . . . precise and perceptive and conscious . . . " —Text and Performance Quarterly "Woman, Native, Other is located at the juncture of a number of different fields and disciplines, and it genuinely succeeds in pushing the boundaries of these disciplines further. It is one of the very few theoretical attempts to grapple with the writings of women of color." —Chandra Talpade Mohanty "The idea of Trinh T. Minh-ha is as powerful as her films . . . formidable . . . " —Village Voice " . . . its very forms invite the reader to participate in the effort to understand how language structures lived possibilities." —Artpaper "Highly recommended for anyone struggling to understand voices and experiences of those 'we' label 'other'." —Religious Studies Review Audio book narrated by Betty Miller. Produced by Speechki in 2021.
Keywords: 1900-1999; approches et analyses; arts; cours; discipline; féminisme autochtone; féminisme décolonial; har4600; histoire de l'art; premier cycle; périodes historiques; ressource en ligne; thématiques; écriture des femmes*; études littéraires

Black art: A discussion - Araeen, Rasheed; Chambers, Eddie (Third Text, 1988)
Keywords: antiracisme; approches et analyses; arts; asie; cours; discipline; europe; har4610; histoire de l'art; premier cycle; royaume-uni; régions géographiques

C'est le soleil qui m'a brûlée - Beyala, Calixthe (J'ai lu. Roman, 1988)
"La tête dans les odeurs de l'homme, la bouche contre son sexe, elle se dit qu'il est devenu complètement fou, qu'elle est devenue complètement folle (...). Dans l'état actuel de l'histoire, quoi qu'elle fasse, quoi qu'elle dise, elle aura toujours tort. L'homme c'est lui." Cameroun. Chaleur humide, ciel hypnotique. Dans le bidonville où elle a grandi, abandonnée par sa mère, Ateba cherche avec désespoir sa place dans une société où la femme n'a qu'un droit : se taire. Ecartelée entre plusieurs sentiments contraires, la jeune fille, le ventre en feu, la haine au coeur, est certaine qu'elle peut devenir un jour la plus forte. Incapable de se résoudre à concilier sexe et asservissement, elle refuse de passer sa vie à genoux.--Quatrième de couverture.
Keywords: afrique; afro-féminisme; approches et analyses; arts; cameroun; cours; discipline; féminisme africain; lit2815; premier cycle; roman; régions géographiques; sexisme; systèmes d'oppressions; études littéraires

Vision and difference femininity, feminism, and histories of art - Pollock, Griselda (Routledge, 1988)
Griselda Pollock provides concrete historical analyses of key moments in the formation of modern culture to reveal the sexual politics at the heart of modernist art. Crucially, she not only explores a feminist re-reading of the works of canonical male Impressionist and Pre-Raphaelite artists including Edgar Degas and Dante Gabriel Rossetti, but also re-inserts into art history their female contemporaries - women artists such as Berthe Morisot and Mary Cassatt. Pollock discusses the work of women artists such as Mary Kelly and Yve Lomax, highlighting the problems of working in a culture where the feminine is still defined as the object of the male gaze.
Keywords: arts; corps; cours; discipline; europe; femmes* artistes; har4600; har4610; histoire de l'art; histoire et politique; premier cycle; représentation des femme*; régions géographiques; thématiques

Écrire dans la maison du père : l'émergence du féminin dans la tradition littéraire du Québec. - Smart, Patricia (Collection Littérature d'Amérique, 1988)
Dans une analyse qui assoit ses bases sur un texte du XIXe siècle (Angélinede Montbrun de Laure Conan), Patricia Smart démontre que, parallèlement à son histoire à lui, il y a une autre histoire, modulée par une autre voix, qui donne à lire une autre perspective sur le pays et sur le réel. Dans cet essai capital, elle nous propose une lecture absolument nouvelle des textes majeurs de la littérature québécoise. Écrire dans la maison dupère fait la preuve qu'en repérant les marques de la différence sexuelle dans le texte québécois, on peut ouvrir de larges brèches dans la thématique nationale et laisser entrevoir une ouverture possible sur un avenir habitable...
Keywords: amériques; arts; cours; cycles supérieurs; discipline; fem1000; fem7000; lit3220; lit3495; premier cycle; québec; régions géographiques; thématiques; théories féministes; écriture des femmes*; études littéraires

In other worlds essays in cultural politics - Spivak, Gayatri Chakravorty (Routledge, 1988)
Dans cet ouvrage classique, Gayatri Chakravorty Spivak, l'une des théoriciennes de la culture les plus importantes et les plus influentes travaillant aujourd'hui, analyse la relation entre la langue, les femmes et la culture dans des contextes occidentaux et non occidentaux. Développant une intégration originale de puissantes méthodologies contemporaines - déconstruction, marxisme et féminisme - Spivak tourne ce nouveau modèle sur les grands débats de l'étude de la littérature et de la culture, assurant ainsi que In Other Worlds est devenu un outil précieux pour étudier notre propre monde et celui des autres cultures.
Keywords: 1900-1999; 1980-1989; arts; cours; cycles supérieurs; discipline; fem1000; fem7000; histoire et politique; international; lit3220; premier cycle; périodes historiques; thématiques; théories féministes; théories littéraires; études littéraires; études postcoloniales

Borderlands: The new mestiza - Anzaldúa, Gloria (Spinsters, Aunt Lute, 1987)
Rooted in Gloria Anzaldúa’s experience as a Chicana, a lesbian, an activist, and a writer, the groundbreaking essays and poems in this volume profoundly challenged how we think about identity. Borderlands/La Frontera remapped our understanding of what a “border” is, seeing it not as a simple divide between here and there, us and them, but as a psychic, social, and cultural terrain that we inhabit, and that inhabits all of us. This twentieth-anniversary edition features new commentaries from prominent activists, artists, and teachers on the legacy of Gloria Anzaldúa’s visionary work
Keywords: amériques; approches et analyses; cours; cycles supérieurs; discipline; fem1000; fem7000; féminisme décolonial; identités LGBTQIA2+; lit3220; littérature; mexique; pol4212; premier cycle; queer; régions géographiques; thématiques; états-unis; études littéraires

Femmes de la rive gauche - Benstock, Shari (Des femmes, 1987)
Femmes de la Rive gauche étudie les contributions à la vie du Paris littéraire entre 1900 et 1940 de grandes Américaines et Anglaises, telles que Djuna Barnes, Natalie Barney, Sylvia Beach, Caresse Crosby, Nancy Cunard, Hilda Doolittle, Janet Flanner, Anaïs Nin, Jean Rhys, Gertrude Stein, Edith Wharton… Écrivain.e.s, éditeurices, libraires, journalistes, tenant salon au cœur du Paris culturel, elles ont nourri de leur énergie créatrice originale le grand mouvement de la modernité. Cet essai, qui considère à la fois l’histoire littéraire et la littérature, écrit la face cachée du tissu culturel, explore la richesse d’une écriture que le modernisme a tenté de nier…. « Au lieu d’intersection de la vie et de l’art, au croisement de la mémoire et de l’histoire, à la confluence du mythe et de la biographie… j’ai retrouvé les traces de celles qui ont nourri de leur force et de leur intelligence le grand mouvement culturel moderniste. » S. B.
Keywords: 1900-1909; 1900-1999; 1910-1919; 1920-1929; 1930-1939; arts; cours; discipline; europe; france; his4860; histoire de l'art; histoire des femmes*; histoire et politique; littérature française; modernité; paris; premier cycle; périodes historiques; régions géographiques; thématiques; écriture des femmes*; études littéraires

Il n'y a pas de cogito-femme - Collin, Françoise (L'émergence d'une culture au féminin, 1987)
Keywords: 1900-1999; 1980-1989; amériques; approches et analyses; cours; cycles supérieurs; discipline; fem1000; fem9000; histoire et politique; interdisciplinarité; philosophie; premier cycle; périodes historiques; québec; régions géographiques; sciences humaines; thématiques; études culturelles; études littéraires

Reading black, reading feminist: A critical anthology - Gates, Henry Louis (Meridian Book, 1987)
A unique and comprehensive collection of 26 literary essays that provides real evidence of the rich cultural history of black women in America. Black women’s writing has finally emerged as one of the most dynamic fields of American literature. Here, leading literary critics—both male and female, black and white—look at fiction, nonfiction, poetry, slave narratives, and autobiographies in a totally new way. In essence, they reconstruct a literary history that documents black women as artists, intellectuals, symbol makers, teachers, and survivors. Important writers whose work and lives are explored include Toni Morrison, Gloria Gaynor, Maya Angelou, and Alice Walker, and the fascinating list of essays range from Nellie Y. McKay’s “The Souls of Black Women Folk in the Writings of W. E. B. Du Bois” to Jewelle L Gomez’s very personal tribute to Lorraine Hansberry as a dramatist and crusader for social justice. Henry Louis Gates Jr., the editor of this anthology and a noted authority on African-American literature, has provided a thought-provoking introduction that celebrates the experience of “reading black, reading feminist.” A penetrating look at women’s writing from a unique perspective, this superb collection brings to light the rich heritage of literary creativity among African-American women.
Keywords: 1900-1999; afro-féminisme; amériques; anthologie; approches et analyses; cours; discipline; fem1000; femmes* noires; féminismes noirs; pratiques féministes; premier cycle; périodes historiques; régions géographiques; thématiques; écriture des femmes*; états-unis; études littéraires

The Feminist Critique of Art History - Gouma-Peterson, Thalia; Mathews, Patricia (The Art Bulletin, 1987)
Art criticism and art history from a feminist perspective are recent phenomena, emerging only during the last fifteen years. They have, in their short history, moved from a first generation in which "the condition and experience of being female" was emphasized, to a second generation, beginning in the late 1970s, influenced by feminist criticism in other disciplines and offering a more complex critique of both art and culture through an investigation of the production and evaluation of art and the role of the artist. In this survey, we propose, first, to outline the history of feminist art and art history, then to discuss the interrelated themes in each, and, finally, in the concluding and pivotal sections (IV and V), to discuss various feminist art-critical and art-historical methodologies.
Keywords: 1900-1999; approches et analyses; art moderne; artistes féministes; arts; corps; cours; critique d'art; discipline; discours dominant; femmes* artistes; har4600; histoire de l'art; histoire et politique; maternité; patriarcat; premier cycle; périodes historiques; représentation; sexisme; sexualité; systèmes d'oppressions; thématiques

Framing feminism: art and the women's movement, 1970-1985 - Parker, Rozsika (Popular culture critical readers, 1987)
Feminism has been a major force in the reshaping of recent art. The women's movement has given new confidence to women who work in the visual arts; it has opened up new areas for art to deal with and challenged existing systems of values and imagery in the arts. In their comprehensive introduction, Rozsika Parker and Griselda Pollock provide a richly illustrated history of the British women's art movement, covering the major events and debates in feminist art practice which have taken place over the last fifteen years. They also examine the trends, the conflicts and the new directions of the 1980s in which issues of race, as well as gender, have necessarily become prominent. Griselda Pollock goes on to explore the place of feminist art in the context of post-modern culture, arguing that feminism is one of the most important and radical interventions in both modernism and post-modernism. --back cover.
Keywords: 1900-1999; 1970-1979; 1980-1989; approches et analyses; arts; cours; discipline; europe; femmes* artistes; har4600; histoire de l'art; histoire et politique; intersectionnalité; postmodernisme; premier cycle; périodes historiques; royaume-uni; régions géographiques; thématiques

Entre l'écriture - Cixous, Hélène (Des femmes, 1986)
Entre l’écriture rassemble sept textes qui, sur une dizaine d’années, de 1975 à 1984, ont posé la question de l’« écriture féminine » : réflexion sur un des points les plus controversés des nouveaux féminismes. Tout en poursuivant une critique aiguë et gaie de l’écriture au masculin, et en donnant parallèlement une œuvre de fiction abondante, Hélène Cixous explore, depuis La Venue à l’écriture, l’espace où s’affirme de la différence. Écrire n’est jamais neutre, le geste, le texte sont sexués : « J’écris-femme. Quelle différence ? » C’est la question que tous ces textes relance, d’une langue à l’autre, d’un sexe à l’autre, de l’art de peindre à l’art d’écrire. La venue à l’écriture.
Keywords: 1900-1999; 1970-1979; 1980-1989; approches et analyses; cours; différence des sexes; discipline; discours dominant; europe; fem1000; france; lit3495; premier cycle; périodes historiques; rapports sociaux de sexe; régions géographiques; systèmes d'oppressions; thématiques; écriture des femmes*; études littéraires

La venue à l'écriture - Cixous, Hélène (Entre l'ecriture, 1986)
Keywords: 1900-1999; 1970-1979; approches et analyses; cours; différence des sexes; discipline; discours dominant; europe; fem1000; france; lit3495; premier cycle; périodes historiques; régions géographiques; systèmes d'oppressions; thématiques; écriture des femmes*; études littéraires

Le livre de la cité des dames - De Pisan, Christine (Série "Moyen Age", 1986)
Traduction, Introduction par Éric Hicks et Thérèse Moreau À la plus italienne des Parisiennes du XVe siècle revint la gloire de défendre l’honneur des femmes : en 1405, Christine de Pizan achevait le Livre de la Cité des dames qui donnait en exemple les femmes illustres de tous les temps. Il y eut ensuite le Livre des trois vertus ou Trésor de la Cité des dames, où Christine faisait une analyse lucide et précise de la société française, vue du côté féminin, détaillant tous les «états des femmes» et donnant de chacun, depuis celui des princesses jusqu’à celui des femmes de laboureur, une vision réaliste et positive. La première, elle avait compris que les femmes avaient une place à elles dans la société politique. Née à Venise vers 1365, Christine vient, à quatre ans, vivre à Paris où son père, Thomas de Pizan, médecin et astrologue, a été appelé par Charles V. Elle défend les femmes en rassemblant un large éventail de femmes célèbres à travers l'histoire. Ces femmes sont «logées» dans la Cité des Dames, qui est en fait le livre. Alors que Pizan construit sa ville, elle utilise chaque femme célèbre comme un élément constitutif non seulement des murs et des maisons de la ville, mais aussi comme éléments constitutifs de sa thèse. Chaque femme ajoutée à la ville ajoute à l'argument de Pizan selon lequel les femmes sont des participantes valorisées dans la société. Elle plaide également en faveur de l'éducation des femmes.
Keywords: cours; discipline; europe; fem1000; histoire; histoire des femmes*; histoire et politique; incontournable; littérature; moyen-âge; occident; premier cycle; périodes historiques; régions géographiques; sciences humaines; thématiques; écriture des femmes*; éducation; études littéraires

Lettres parisiennes: histoires d'exil - Huston, Nancy; Sebbar, Leïla (J'ai lu, 1986)
Pendant plus d'un an, deux femmes se sont écrit. L'une est née au Canada anglais, l'autre en Algérie française. A Paris, étrangères en exil, elles ont choisi de travailler, d'aimer, d'avoir des enfants. Elles ne sont ni d'ici, ni de là-bas. Leur pays est celui du verbe. Elle cherchent en tâtonnant ce sentiment d'appartenance qui leur permettrait de réaliser leur destin : celui d'écrivain.--Quatrième de couverture.
Keywords: 1900-1999; afrique; algérie; amériques; arts; canada; cours; discipline; europe; france; immigration; lit3220; littérature; premier cycle; périodes historiques; régions géographiques; thématiques; écriture des femmes*; études littéraires

La lettre aérienne - Brossard, Nicole (Les éditions du remue-ménage, 1985)
Lieu d’invention, laboratoire où s’élaborent une pensée originale et la recherche d’un langage inédit, La lettre aérienne rassemble douze essais de Nicole Brossard écrits entre 1975 et 1985. Ces textes témoignent de la quête individuelle de l’écrivaine, ancrée dans l’histoire, dans l’affirmation de la modernité québécoise et l’émergence d’une culture affranchie de la norme patriarcale.
Keywords: amériques; approches et analyses; arts; cours; discipline; fem1000; identités; identités LGBTQIA2+; lesbianisme; lit3495; littérature; premier cycle; québec; régions géographiques; thématiques; écriture des femmes*; études littéraires

La compagnie des loups: et autres nouvelles - Carter, Angela (Seuil, 1985)
Ils sont tous là, si familiers... et pourtant étrangement pervertis. Barbe-Bleue, le petit Chaperon rouge, la Belle et la Bête, le loup-garou, Blanche-Neige... chargés de violence et d'un érotisme gothique, parés d'une morale différente et d'une beauté nouvelle. Attention, les loups sont parmi nous, mais aussi en nous, prêts à bondir...
Keywords: 1900-1999; 1970-1979; arts; contes; cours; discipline; europe; fem1000; littérature; premier cycle; périodes historiques; royaume-uni; régions géographiques; sexualité; thématiques; études littéraires

Le cabinet sanglant - Carter, Angela (La Compagnie des loups, 1985)
Keywords: 1900-1999; 1980-1989; contes; cours; discipline; europe; fem1000; littérature; premier cycle; périodes historiques; royaume-uni; régions géographiques; sexualité; sofia; thématiques; études littéraires

Women artists in history: from antiquity to the 20th century - Slatkin, Wendy (Prentice-Hall, 1985)
"The careers and accomplishments of women creators in Western Civilization are described in an accessible and informative mattner in the Second Edition of Women Artists in History: From Antiquity to the 20th Century. Over sixty artists, mostly painters and sculptors, are featured in this book. Selections were based on each woman's unique and important contributions to the history of art. each artist measures up to the same rigorous standards applied to male artists in other survey texts. To understand and appreciate the achievements of these outstanding women, this volume takes a thorough look at the cultural environment in which they lived and worked, as well as the social, economic, and demographic factors that influenced their art." --From back cover
Keywords: 1500-1599; 1600-1699; 1700-1799; 1800-1899; 1900-1999; antiquité; arts; biographie; cours; discipline; femmes* artistes; har4600; histoire de l'art; histoire et politique; moyen-âge; premier cycle; périodes historiques; thématiques

Dreams, Demands, and Desires : The Black, Antiwar, and Women’s Movements - Studio Museum in Harlem; Lippard, Lucy (Tradition and conflict images of a turbulent decade: 1963-1973, 1985)
Essay in a catalogue for an exhibition that is considered a key survey of how Black art was inspired or affected by the civil rights movement.
Keywords: 1900-1999; 1960-1969; 1970-1979; amériques; approches et analyses; arts; cours; discipline; har4610; histoire de l'art; histoire et politique; intersectionnalité; premier cycle; périodes historiques; représentation des femme*; régions géographiques; thématiques; états-unis

L'amant - Duras, Marguerite (Les Éd. de Minuit, 1984)
Dans l'ambiance languissante de l'Indochine coloniale des années 1930, entre forêt et fleuve, une jeune blanche qui n'a pas seize ans découvre le plaisir avec un riche chinois et s'arrache progressivement à une insupportable famille. Le plus autobiographique des récits de l'auteure. Le récit d'une passion charnelle, scandaleuse et sans avenir (mais quelle passion s'inquiète de l'avenir?).
Keywords: 1900-1999; 1930-1939; arts; asie; cours; discipline; indochine; lit2815; premier cycle; périodes historiques; régions géographiques; sexualité; thématiques; écriture des femmes*; études littéraires

Quand je lis, je m'invente : essai - Lamy, Suzanne (L'Hexagone, 1984)
Les deux livres de Suzanne Lamy réunis ici démontrent clairement toute la contemporanéité des écrits de celle qui a contribué à l'implantation du discours féministe au Québec. On n'a qu'à ouvrir le livre au hasard des pages pour constater la pertinence et l'actualité des propos de l'essayiste en un temps où la parole féministe a bien besoin de ses racines. Le prouve aussi cet extrait de la main de l'auteure : « Je suis violente et j'ai horreur de la violence. Horreur des violences qui m'ont été faites et qui sont tapies en moi, couchées là, endormies et prêtes à se relever, à courir comme de grandes folles, irrépressibles, mauvaises comme des eaux déchaînées. Ces violences, je n'ai pu les tuer, on ne tue pas la violence, on ne l'évacue pas, on l'occulte, on la range, mais elle est là, indocile, indomptable. »
Keywords: 1900-1999; 1980-1989; amériques; cours; discipline; fem1000; littérature; premier cycle; périodes historiques; québec; régions géographiques; thématiques; écriture des femmes*; études littéraires

Une Histoire des femmes est-elle possible? - Perrot, Michelle (Rivages, 1984)
Les femmes ont-elles une histoire ? Pourquoi cette histoire n’a-t-elle pas été écrite dans le passé et pourquoi se développe-t-elle depuis une dizaine d’années ? De quelles sources dispose-t-on à cet égard et cette démarche implique-t-elle des méthodes particulières ? Que signifient « mémoire », « culture », « pouvoir » des femmes ? La catégorie de sexe est-elle, comme celle des âges, une variable historique issue des nouveaux classements induits par le développement de l’individualisme ? ou quelque chose de plus ? Voilà quelques unes des questions abordées dans ce livre qui prend en compte le changement de direction du regard historique lorsque l’on pose la question du rapport des sexes comme central. Avec la participation d’Alain Corbin, Arlette Farge, Agnès Fine, Catherine Fouquet, Geneviève Fraisse, Christiane Klapisch, Yvonne Knibiehler, Michelle Perrot, Elisabeth Ravoux-Rallo, Jacques Revel, Anne Roche, Pauline Schmitt-Pantel, Sylvie Van de Casteele, Danièle Voldman.
Keywords: arts; cours; discipline; france; har4600; histoire de l'art; histoire et politique; premier cycle; thématiques

American women artists, past and present: a selected bibliographic guide - Tufts, Eleanor (Garland reference library of the humanities, 1984)
Keywords: amériques; arts; bibliographie; cours; discipline; femmes* artistes; har4600; histoire de l'art; histoire et politique; pol4022; premier cycle; régions géographiques; thématiques; états-unis

La place - Ernaux, Annie (Gallimard, 1983)
«Récit remarqué par la critique. L'ombre du père et la genèse d'un remord, celui d'une intellectuelle d'origine modeste devenue "bourgeoise". Prix Renaudot 1984.»-- [SDM].
Keywords: 1900-1999; arts; cours; discipline; disicpline; europe; filiation; france; lit2815; premier cycle; périodes historiques; roman; régions géographiques; thématiques; transfuge de classe; écriture des femmes*; études littéraires

The Anti-aesthetic: essays on postmodern culture - Foster, Hal (Bay Press, 1983)
For the past thirty years, Hal Foster has pushed the boundaries of cultural criticism, establishing a vantage point from which the seemingly disparate agendas of artists, patrons, and critics have a telling coherence. In The Anti-Aesthetic, preeminent critics such as Jean Baudrillard, Rosalind Krauss, Fredric Jameson, and Edward Said consider the full range of postmodern cultural production, from the writing of John Cage, to Cindy Sherman's film stills, to Barbara Kruger's collages. With a redesigned cover and a new afterword that situates the book in relation to contemporary criticism, The Anti-Aesthetic provides a strong introduction for newcomers and a point of reference for those already engaged in discussions of postmodern art, culture, and criticism. Includes a new afterword by Hal Foster and 12 black and white photographs.
Keywords: 1900-1999; 1950-1959; 1960-1969; 1970-1979; 1980-1989; approches et analyses; arts; corps; cours; discipline; femmes* artistes; har4600; histoire de l'art; postmodernisme; premier cycle; périodes historiques; thématiques

L'avant-garde au feminin: Moscou, Saint-Petersbourg, Paris : 1907-1930 - Marcadé, Jean-Claude; Marcade, Valentine (Artcurial, 1983)
Paris, Artcurial, 1983, broché sous couverture illustrée, 64 pp., (27,5 x 21 cm). Exposition mai-juillet 1983. Importante illustration couleur et noir et blanc (reproductions et photographies). Biographie sommaire autour des artistes :Sonia DELAUNAY, Alexandra EXTER, Marie VASSILIEFF, Marianne WEREFKIN, Natalia GONTCHAROVA, Lioubov POPOVA, Nadiejda OUDALTSOVA, Olga ROZANOVA, Nina KOGAN, Vera PESTEL, Vera ERMOLAIEVA, Xenia ENDER, etc.
Keywords: 1900-1999; 1910-1919; 1920-1929; approches et analyses; art moderne; arts; cours; discipline; discours dominant; europe; femmes* artistes; france; har4600; histoire de l'art; histoire et politique; moscou; paris; premier cycle; périodes historiques; russie; régions géographiques; saint-petersbourg; sexisme; systèmes d'oppressions; thématiques

La Québécoite: roman - Robin, Régine (Collection Littérature d'Amérique, 1983)
Sous le regard de l'Autre. Par l'auteure d'Histoire et linguistique (Colin, 1973) et d'une étude sur l'écriture juive (Le Sorbier, 1983), un récit dans lequel ce professeur d'université française, d'origine judéo-russe, qui enseigna à Montréal, Laval et Sherbrooke relate, pour le bénéfice de ses étudiants, l'histoire de sa découverte du Québec entre 1974 et 1981. Régine Robin, de formation marxiste, manifeste une attention particulière aux luttes ouvrières (grèves, etc.), politiques, idéologiques. L'éditeur parle avec justesse d'un livre d'émigrante sur l'exil, la langue et la vie d'ici. Composition en mosaïque. Inventaires, comparaisons, fragments, altérités.
Keywords: 1900-1999; 1970-1979; 1980-1989; amériques; arts; cours; discipline; disicpline; histoire et politique; immigration; lit3495; premier cycle; périodes historiques; québec; régions géographiques; thématiques; écriture des femmes*; études littéraires

The Amazing decade: women and performance art in America : 1970-1980 - Roth, Moira; Jacob, Mary Jane; Roth, Moira (Astro Artz., 1983)
"This book is a detailed study of the powerful and innovative role women artists played in the development and expansion of performance art. This hybrid art form, which combines the visual arts with ingredients drawn from experimental dance, theater, music, and poetry, emerged in the late 1960's at the same time as the women's movement. Many women artists turned to performance art in order to translate and capture visually the concerns, demands and visions of the women's movement; thus women led the way in performance art's explorations of autobiography, ritual, mass spectacle and the creation of characters and personae. The Amazing Decade, edited by Moira Roth, with an introduction by Mary Jan Jacob, culls the best from women's performance history, highlighting pivotal works, chronicling changes and projecting future directions: the book contains a major essay by Roth on the history and character of women's performance art; individual profiles on thirty-seven artists and collectives; an extensive bibliography; and a year-by-year chronology from 1956 onward in which women's performance art is set in the context of history and the women's movement. Profusely illustrated, The Amazing Decade is an indispensable reference book and an invaluable teaching tool"--
Keywords: 1900-1999; 1970-1979; amériques; approches et analyses; artistes féministes; arts; cours; discipline; femmes* artistes; féminisme pop; har4600; histoire de l'art; histoire et politique; performance; premier cycle; périodes historiques; régions géographiques; thématiques; états-unis

In search of our mothers' gardens womanist prose - Walker, Alice (Harcourt Brace, 1983)
In this, her first collection of nonfiction, Alice Walker speaks out as a black woman, writer, mother, and feminist. Among the thirty-six pieces are essays about other writers, accounts of the civil rights movement of the 1960s and the anti-nuclear movement of the 1980s, and a vivid memoir of a scarring childhood injury and her daughter’s healing words.
Keywords: 1900-1999; amériques; approches et analyses; arts; cours; cycles supérieurs; discipline; droits civiques; fem1000; fem3300; fem7000; histoire et politique; lit3220; littérature; premier cycle; périodes historiques; régions géographiques; thématiques; womanist; états-unis; études littéraires

Art et féminisme - Arbour, Rose-Marie; Murgia, Pierre; Musée d'art contemporain (Québec); Arbour, Rose-Marie; Murgia, Pierre; Musée d'art contemporain (Québec) (Ministère des affaires culturelles, 1982)
Catalogue de l'exposition Art et féminisme qui eut lieu en 1982 au Musée d'Art Contemporain de Montréal (MAC).
Keywords: 1900-1999; 1970-1979; 1980-1989; amériques; arts; arts visuels et médiatiques; canada; cours; discipline; femmes* artistes; har4600; histoire de l'art; histoire et politique; premier cycle; périodes historiques; québec; régions géographiques; thématiques

Feminism and art history: questioning the litany - Broude, Norma; Garrard, Mary D. (Icon editions, 1982)
A long-needed corrective and alternative view of Western art history, these seventeen essays by respected scholars are arranged chronologically and cover every major period from the ANcient 2gypt to the present. While several of the essays deal with major woman artists, the book is essentially about western art history and the extent to which it has been distorted, in every period, by sexual bias. With 306 illustrations.
Keywords: 1500-1599; 1600-1699; 1700-1799; 1800-1899; 1900-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; Feminism and art; Feminism in art; amérique du nord; amériques; antiquité; arts; cours; discipline; europe; femmes* artistes; har4600; histoire de l'art; histoire et politique; moyen-âge; occident; premier cycle; périodes historiques; régions géographiques; thématiques

L'autre moitié de l'avant-garde: 1910-1940: femmes peintres et femmes sculpteurs dans les mouvements d'avant-garde historiques - Vergine, Lea (Des Femmes, 1982)
L'autre moitié de l'avant-garde, 1910-1940 est une importante exposition qui s'est tenue à Milan au printemps 1980, puis à Rome, Venise, Amsterdam, Stockholm. D'une rare qualité, elle a remis à jour les démarches et recherches qui, dans la période féconde des années 1930, ont été fondamentales pour l'élaboration d'un langage contemporain. « Préparer ce travail a été, pour moi, une découverte continue : quinze mois passés à chercher dans les caves des musées, à faire ouvrir aux artistes leurs tiroirs. Rares sont les oeuvres que j'ai trouvées accrochées à un mur ! [...] L'exposition évoque les années du Blaue Reiter, du cubisme, du futurisme, du dadaïsme, du Bauhaus. Je voulais voir si les femmes avaient eu ou non, dans ces groupes, la possibilité d'être des forces motrices. Et j'ai découvert, par exemple, que dans l'avant-garde russe, les femmes ont eu un rôle tout à fait décisif...» L.V. Le catalogue rassemble ces monographies, largement illustrées des productions des femmes peintres et sculptrices, et retrace ces mouvements novateurs.
Keywords: 1900-1999; 1910-1919; 1920-1929; 1930-1939; approches et analyses; arts; cours; discipline; europe; femmes* artistes; har4600; histoire de l'art; histoire et politique; premier cycle; périodes historiques; régions géographiques; sexisme; systèmes d'oppressions; thématiques

Femmes peintres: 1550-1950 - Harris, Ann Sutherland; Nochlin, Linda (Ed. des femmes, 1981)
Catalogue d'exposition. Il s'agit de la première exposition rassemblant les oeuvres de femmes peintres, organisée au Los Angeles Country Museum of Art par Ann Sutherland Harris, conservateur au Metropolitan Museum of Art de New York et Linda Nochlin, enseignante en histoire de l'art à l'université de Vassar. Ces oeuvres jusque-là dispersées dans divers musées et collections privées, et rassemblées dans cette exposition et ce catalogue devenu un ouvrage de référence, font apparaître la place des femmes et leur influence parfois marquante dans l'histoire de l'art occidental. D'Italie en Flandres, en France, en Allemagne, en URSS, aux États-Unis, la vie et l'oeuvre de : Catherina Van Hemessen, Sofonisba Anguissola, Fede Galizia, Judith Leyster, Clara Peeters, Élisabeth Vigée Le Brun, Rosa Bonheur, Sonia Delaunay... Et bien d'autres.
Keywords: 1500-1599; 1600-1699; 1700-1799; 1800-1899; 1900-1909; 1900-1999; 1910-1919; 1920-1929; 1930-1939; 1940-1949; amérique du nord; amériques; arts; arts visuels et médiatiques; cours; discipline; europe; femmes* artistes; har4600; histoire de l'art; histoire et politique; incontournable; peinture; premier cycle; périodes historiques; régions géographiques; thématiques

Old mistresses: Women, art and ideology - Parker, Rozsika; Pollock, Griselda (Pantheon Books, 1981)
How was it possible, by the later twentieth century, to have erased women as artists from art history so comprehensively that the idea of 'the artist' was exclusively masculine? Why was this erasure more radical in the twentieth century than ever before? Why is everything that compromises greatness in art coded as 'feminine'? Has the feminist critique of Art History yet effected real change? With a new Preface by Griselda Pollock, this new edition of a truly groundbreaking book offers a radical challenge to a women-free Art History. Parker and Pollock's critique of Art History's sexism leads to expanded, inclusive readings of the art of the past. They demonstrate how the changing historical social realities of gender relations and women artists' translation of gendered conditions into their works provide keys to novel understandings of why we might study the art of the past. They go further to show how such knowledge enables us to understand art by contemporary artists who are women and can contribute to the changing self-perception and creative work of artists today.
Keywords: LGBTQIA2+; approches et analyses; art féministe; arts; cours; discipline; fem1000; genre; har4600; histoire de l'art; histoire et politique; identités LGBTQIA2+; premier cycle; sexisme; stéréotypes; systèmes d'oppressions; thématiques

Issue: social strategies by women artists - Lippard, Lucy R.; Institute of Contemporary Arts (Londres, Angleterre) (Institute of Contemporary Arts, 1980)
Catalogue for the exhibition Issue: social strategies by women artists, which took place in 1980 at the ICA, in London UK. Lucy Lippard, the exhibition’s organiser, described this as ‘the first establishment-approved women’s show in London’.36 She conceived it as ‘a framework for a transatlantic and cross-cultural dialogue’ about feminist art practice, and responses to various issues including ecology, unemployment, war and violence against women. The exhibition included many American women artists, including: Ariadne: A Social Art Network (Suzanne Lacy and Leslie Labowitz), Candace Hill-Montgomery, Jenny Holzer, Maria Karras, Mary Kelly, Margia Kramer, Beverly Naidus, Adrian Piper, Martha Rosler, Bonnie Sherk, Nancy Spero, May Stevens and Mierle Laderman Ukeles. Kelly, an American artist resident in England for many years, sensed that ‘in most of the work by American artists ... any emphasis on the “personal” appeared to detract from what they would consider “wider social issues”’.37 In this she distinguished it from European feminist work in which ‘the social and the psychic haven't been seen as necessarily antagonistic or contradictory’.
Keywords: 1900-1999; 1970-1979; amériques; artistes féministes; arts; arts visuels et médiatiques; cours; discipline; europe; femmes* artistes; har4600; histoire de l'art; histoire et politique; premier cycle; périodes historiques; royaume-uni; régions géographiques; sex1911; thématiques; états-unis